Access to irrigation and the escape from poverty: Evidence from Northern Mali - Dillon, Andrew (International Food Policy Research Institute, 2008)
Significant changes in the agricultural sector in northern Mali suggest that irrigation has made a large contribution to welfare increases over the past eight years. Using difference-in-differences, propensity score matching, and matched difference in differences with a small panel, this study estimates the impact of access to irrigation on poverty, production, and nutrient intakes. The findings suggest that gains in agricultural production value do not transfer uniquely to household consumption. The paper tests two alternative hypotheses about the distribution of agricultural gains: (1) the gains in agricultural production induced by irrigation yield higher household savings, or (2) intra-village transfers from irrigators to non-irrigators contribute to informal social insurance. The paper provides evidence of both saving and sharing within villages as complimentary strategies for consuming gains in agricultural production. This finding suggests that estimating the effects of a program, relying solely on household consumption, may underestimate the welfare gains of irrigation investment by ignoring the household?s savings and informal insurance network.